Dissolution and suspension of asphaltenes with ionic liquids. (15th February 2019) - Zheng, Ce; Brunner, Manuel; Li, Hua; Zhang, Dongke; Atkin, Rob
Graphical abstract: Highlights: Treatment results of asphaltenes with 16 different ionic liquids were investigated. Two oil-miscible ionic liquids BTMPP and BEHP were most effective. Ionic liquid hydrophobicity was shown to play a key role for asphaltene treatment. Asphaltenes recovered from BTMPP and BEHP decomposed at lower temperatures. Abstract: Asphaltenes, which comprise polycyclic aromatic hydrocarbon cores with attached short aliphatic side chains, are the most polar fraction of crude oils. Asphaltenes are prone to precipitation, which requires expensive cleaning procedures using solvents like toluene or xylene. The toxicity and high vapour pressures of toluene and xylene means there is an urgent need for new liquids that are able to dissolve or suspend asphaltenes but are less environmentally problematic. This study reports treatment results of asphaltenes with 16 different ionic liquids covering three different types of cation charge groups, namely, cholinium, imidazolium and phosphonium with a wide variety of anions. The two oil-miscible ionic liquids, trihexyl(tetradecyl)phosphonium bis(2, 4, 4-trimethylphentyl)phosphinate and trihexyl(tetradecyl)phosphonium bis(2-ethylhexyl)phosphate, solubilised or suspended a significant fraction of raw asphaltenes. Elemental analysis, TGA and FTIR revealed that asphaltenes recovered from these ionic liquids had increased aliphatic and oxygen content compared to the raw material, and decomposed at lower temperatures during TGA test. The relative hydrophobicity of the ionic liquid is the major factor controlling the asphaltene mass in the ionic liquid, followed by the strength of interactions between ionic liquid and asphaltene alkyl groups. These findings provide a platform for the development of new ionic liquid based cleaners for asphaltene deposits.